2002
DOI: 10.1038/416823a
|View full text |Cite
|
Sign up to set email alerts
|

The acceleration of cosmic-ray protons in the supernova remnant RX J1713.7–3946

Abstract: Protons with energies up to ~ 10 15 eV are the main component 1 of cosmic rays, but evidence for the specific locations where they could have been accelerated to these energies has been lacking 2 . Electrons are known to be accelerated to cosmic-ray energies in supernova remnants 3,4 , and the shock waves associated with such remnants, when they hit the surrounding interstellar medium, could also provide the energy to accelerate protons. The signature of such a process would be the decay of pions (π 0 ), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
197
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(202 citation statements)
references
References 16 publications
4
197
0
1
Order By: Relevance
“…RX J1713-3946 was also detected in very high-energy (VHE: >100 GeV) γ-rays with the CANGAROO (Muraishi et al 2000;Enomoto et al 2002) and HESS telescopes (Aharonian et al 2004(Aharonian et al , 2006. Especially the latter, very detailed observations show a clear shell structure at TeV energies that correlates well with the ASCA contours.…”
Section: Introductionsupporting
confidence: 57%
“…RX J1713-3946 was also detected in very high-energy (VHE: >100 GeV) γ-rays with the CANGAROO (Muraishi et al 2000;Enomoto et al 2002) and HESS telescopes (Aharonian et al 2004(Aharonian et al , 2006. Especially the latter, very detailed observations show a clear shell structure at TeV energies that correlates well with the ASCA contours.…”
Section: Introductionsupporting
confidence: 57%
“…It is particularly intriguing that the TeV -ray distribution largely resembles that of the CO distribution in that they are enhanced in the northwestern rim of the SNR as noted by Aharonian et al (2004). While the statistical significance in HESS results may not yet be high enough to make a detailed comparison of the individual peaks, we make a preliminary estimate of the efficiency for proton acceleration over the entire SNR by using a formula from Enomoto et al (2002), (E/10 48 )(M cloud /200)(l/3) À3 (d/1) À5 ¼ 1:35, where E (ergs) is the total energy of cosmic-ray protons, M cloud (M ) the molecular cloud mass interacting with them, l ( pc) the typical length of the cloud, and d (kpc) the distance, the same as that in Paper I. We assume that the interacting molecular cloud mass amounts to $2500 M by summing up the major CO peaks in contact with the SNR (from Table 1).…”
Section: Origin Of Gamma Rays and Cosmic-ray Protonsmentioning
confidence: 99%
“…Uchiyama et al (2003) showed that the synchrotron cutoff energy is unusually high beyond 10 keV, corresponding to 10 14 eV as the highest particle energies. G347.3À0.5 was also detected at the TeV -ray range with the CANGAROO telescope (Muraishi et al 2000;Enomoto et al 2002), and models of broadband emission point to IC scattering as the origin of the TeV -ray photons (Muraishi et al 2000;Ellison et al 2001). More recently, follow-up TeV -ray observations have led to a different conclusion, suggesting pion decay as the source of energetic photons ( Enomoto et al 2002), but the nature of this emission is still uncertain (see Butt et al 2002;Reimer & Pohl 2002;Aharonian et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The steep photon spectra has been found in the high energy gamma-ray spectra of some other remnants measured by, e.g., the CANGAROO (Enomoto et al 2002), H.E.S.S (Aharonian et al 2006) and MAGIC (Carmona 2011) atmospheric Cherenkov telescopes. Particles accelerated by DSA mechanism generally comprised two distinct populations -CRs confined in the accelerator and the CRs escaping the system and these two populations have very different spectral shapes.…”
Section: Gamma-ray Observationsmentioning
confidence: 96%